Bioremediation of heavy metals in palm oil mill effluent (POME) using Chlorella vulgaris: A biological approach - Hemen Emmanuel Jijingi; Sara Kazemi Yazdi; Yousif Abdalla Abakr; Azalea Dyah Maysarah Satya (Cleaner Water, 2025)
Palm oil mill effluent (POME) poses a significant threat to water and soil ecosystems due to high loads of organic pollutants and toxic heavy metals such as copper (Cu), cadmium (Cd), iron (Fe), and zinc (Zn). This study evaluates Chlorella vulgaris as a sustainable microalgal solution for heavy metal bioremediation in POME under two cultivation conditions: POME plus synthetic growth medium plus C. vulgaris (PSC, 2:1) and POME plus C. vulgaris (PC, 1:1), alongside a control. Heavy metal concentrations were quantified over 14 days using atomic absorption spectrophotometry, validated with calibration curves showing strong linearity (e.g., Cu: Abs = 0.05504 Conc. + 0.011839, R² = 0.9746; Cd: Abs = 0.26909 Conc. + 0.012259, R² = 0.9637). Removal followed triphasic kinetics: rapid adsorption onto cell-wall functional groups, intracellular bioaccumulation mediated by phytochelatins, and a residual polishing phase. Maximum removal efficiencies reached 98.99 % (Cu), 99.24 % (Cd), 99.29 % (Fe), and 99.92 % (Zn) for PSC. ANOVA confirmed significant effects of treatment condition and time on metal concentration reduction (e.g., Cu: F = 35.29–166.48, P < 0.000001). Under optimum PSC (2:1) culture conditions, maximum removal efficiencies were achieved, reaching 98.99 % for Cu, 99.24 % for Cd, 99.29 % for Fe, and 99.92 % for Zn within 14 days, significantly outperforming the PC (1:1) setup. The pseudo-second-order kinetic model (R² > 0.95) described the adsorption process, confirming chemisorption dominance. The results demonstrate that nutrient-enhanced C. vulgaris cultures provide a cost-effective, green strategy for POME heavy metal removal while generating valuable biomass, supporting circular bioeconomy practices.